Molecularly Engineered Hierarchical Nanodisc from Antiparallel J‐stacked BODIPY Conjugates: Application to Theranostics with Mutually Beneficial Properties. (8th December 2020) - Yan, Xiaosa; Su, Meihui; Liu, Yanan; Zhang, Yongkang; Zhang, Hao; Li, Changhua
Abstract: The J‐aggregation of dye‐functional group conjugates, which results in intriguing photophysical properties and highly ordered structures, has several advantages over that of monomeric dyes and exhibits augmented performance compared to that of monomeric functional groups, thereby providing a novel platform for devising materials with advanced functions. Herein, it is reported that a molecularly engineered nanodisc by the antiparallel J‐aggregation of halogenated BODIPY‐Gd(III), a dye‐functional group conjugate. The highly directional halogen‐bonding interactions enable a unique antiparallel J‐stacking of BODIPY‐Gd(III), resulting in an alternating, orderly arrangement of the functional Gd(III) groups on the surfaces of the nanodisc, and allowing water stability and an enhanced magnetic resonance signal. Moreover, the J‐stacked dyes render the nanodisc with excellent photothermal performance, such as intense NIR‐absorptivity, high photothermal conversion efficiency, and a nearly non‐photobleaching capability. Preliminary in vivo studies demonstrated the potential of the nanodisc as an efficient bimodal photoacoustic and high‐performing magnetic resonance imaging, and antitumor photothermal therapy agent. This conceptual work not only establishes a general strategy for nano‐J‐aggregates with desired dye arrangement, controlled size, and in vivo stability, but also advances the antiparallel J‐aggregation of dye‐functional group conjugates as a potential platform for multifunctional integration and modulation, wherein multiple functional groups and BODIPYs can be installed. Abstract : A water‐stable hierarchical nanodisc is molecularly engineered from antiparallel J‐stacked BODIPY‐Gd(III) conjugates. The halogen bonding‐driven J‐aggregation of BODIPY moiety enables superb photothermal performance, while the alternating and orderly arrangement of the conjugated Gd(III) allows augmented MR signals. Efficient bimodal PA/MR imaging and antitumor photothermal therapy are demonstrated in vivo.